Impact of Various Organic, Inorganic Nutrient Sources and Bio-fertilizers on Growth, Yield, and Post Harvest Soil Status of Soybean - Gawali, D. M.; Narkhede, W. N.; Khazi, G. S. (International Journal of Bio-resource and Stress Management, 2016)
a A field experiment was carried out on clayey soil at the experimental farm, AICRP on Integrated Farming Systems, VNMKV, Parbhani, India during kharif 2015 to evaluate the to study the effect of various organic, inorganic nutrient sources and bio fertilizers on growth yield, yield attributes and post harvest soil status of soybean. The experiment was laid down in split plot design with 18 treatment combinations comprising of two FYM levels i.e. 2.5 t FYM ha-1, 5 t FYM ha-1; three nutrient levels i.e. 75% RDF (22.5:45:22.5 NPK kg ha-1), 100% RDF (30:60:30 NPK kg ha-1) and 125% RDF (37.5:75:37.5 NPK kg ha-1) as main plot treatments and three bio fertilizers i.e. Rhizobium, PSB and Rhizobium+PSB as sub-plot treatments. Application of 5 t FYM ha-1, 125% RDF and Rhizobium+PSB recorded significantly higher plant growth attributing characters viz., Plant height (54.56 cm), number of functional leaves (21.37), leaf area (1323.47 cm2), number of branches (6.46), dry matter accumulation plant-1 (32.61 g) and as well as yield contributing characters viz., number of pods plant-1 (34.26), no. of seeds plant-1 (74.70), seed (1409 kg ha-1), straw (1763 kg ha-1) and biological yield (3172 kg ha-1). The nutrient status after harvest of soybean was highest in the treatment combination of receiving 5 t FYM ha-1, 125% RDF (37.5:75:37.5 NPK kg ha-1), Rhizobium+PSB.